Dodatkowe źródła dochodów bibliotekarzy w Polsce - Milewska, Paulina (Acta Universitatis Lodziensis. Folia Librorum, 2014)
Librarians are a poorly paid occupational group in Poland. Even though most librarians have higher education, their chances for satisfying wages are very small. Under such circumstances librarians are forced to look for additional income sources. This article presents the results of a survey on additional income sources of librarians. The survey was conducted in the end of 2011. The results' analysis is preceded by a short description of the situation on the Polish labor market.